Study of clinical, electrocardiographic and echocardiographic profile in patients with chronic obstructive pulmonary disease - Chaudhari, Rajan; Shrimali, Lalit (International Journal of Research in Medical Sciences, 2018)
Background: Chronic obstructive pulmonary disease is the fourth leading cause of mortality worldwide. It is defined as a disease formal categorized by airflow limitation that is not fully reversible. Patients with chronic obstructive pulmonary disease (COPD) are at increased risk of cardiovascular disease. Electrocardiography (ECG) carries information about cardiac disease and prognosis in COPD patients. However, Echocardiography provides a rapid, noninvasive, portable, and accurate method to evaluate cardiac functions. Methods: A 100 patients of COPD fulfilling the inclusion criteria coming to OPD/wards of Medicine, Gitanjali medical college and Hospital, Udaipur were recruited. They were staged by pulmonary function test (PFT) and evaluated by electrocardiography and echocardiography. Statistical analysis of correlation was done with chi square test and statistical significance was taken p<0.05. Results: Mean age was 52.54±9.55 years, with male preponderance, male to female ratio 4.55:1. Mean duration of disease was 6.36±4.14 years. The common symptoms were Breathlessness (100%). Most common ECG and ECHO finding was RAD (52%) and PAH (54%) respectively. Statistically Right axis deviation and Poor ‘r’ wave progression was significantly correlated with disease severity by ECG findings while R.A. dilatation, R.V. dilatation and Pulmonary hypertension were significantly correlated with disease severity by ECHO findings (p<0.05). Conclusions: COPD is more common in males and in the 5th and 6th decade of life. Most of the patients have fairly advanced disease at presentation. The incidence of abnormalities of ECG and echocardiography increases with COPD severity. ECG and echocardiography are better tools than clinical methods in detecting R.V. dysfunction in COPD.